PENGARUH MODEL PEMBELAJARAN STEM TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII SMP NEGERI 1 TINAMBUNG - Nursakina, Nursakina; Herna, Herna; AR, Rezki Amaliyah (INSPIRAMATIKA, 2023)
The purpose of this study was to determine whether the understanding of mathematical concepts in class VIII students of SMP Negeri 1 Tinambung who were taught using the STEM learning model was higher than the understanding of mathematical concepts in class VIII students of SMP Negeri 1 Tinambung who were taught using the direct learning model. This type of research is a quasi-experimental with a nonequivalent control group design which was carried out at SMP Negeri 1 Tinambung for the 2022/2023 academic year. The sampling technique used was cluster random sampling with class VIII A as the experimental class and class VIII B as the control class. Data collection techniques include tests, observations and questionnaires. While the data analysis techniques used descriptive analysis and inferential analysis. Based on the results of descriptive analysis it can be concluded that students' understanding of mathematical concepts taught using the STEM learning model is included in the good category, students' understanding of mathematical concepts taught using the direct learning model is included in the sufficient category. Then, the result of inferential analysis, show that students' understanding of mathematical concepts taught using the STEM learning model higher than the understanding of students' mathematical concepts taught using direct learning models.